Giant retroperitoneal schwannoma removed with the laparoscopic approach: A case report - Özveri, Emel; Tekcan Şanlı, Deniz Esin; Ertem, Metin (Journal of Surgery and Medicine, 2021)
Retroperitoneal tumors are extremely rare and the vast majority are malignant tumors. One of the least determined benign retroperitoneal tumors is schwannoma. We report the case of a 64-year-old male patient who had a solid mass in the left infrarenal space shown by computed tomography (CT). Percutaneous CT-guided biopsy of the mass was performed, and histopathological examination revealed a schwannoma. The mass was resected laparoscopically. Surgical resection of retroperitoneal tumors is difficult due to posterior deep location and adjacent major vessels and nerves. The laparoscopic approach for retroperitoneal tumors may allow better visualization of the surgical field, reduction of postoperative pain, and better cosmesis. Laparoscopy seems to be a safe and feasible method in the treatment of schwannomas and other retroperitoneal tumors.